EFEKTIVITAS MODEL PEMBELAJARAN LEARNING CYCLE BERBANTUAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) PADA POKOK BAHASAN LOGIKA MATEMATIKA TERHADAP HASIL BELAJAR KELAS X SMA NEGERI 1 TERISI – INDRAMAYU - muhammad winarno; Toheri Toheri; hendri raharjo (EduMa: Mathematics education learning and teaching, 2015)
Learning output of students is essential part of for success of learning proccess. In math,  mainly,  teachers today  apply  expository method  taking  students into  passive classroom learning. Thus, by applying assisted learning cycle LKPD (student’s text book) it is hoped that student’s clasroom learning output is improved. The aim of the research is to investigate learning model of assisted learning cycle LKPD on main logic in improving learning output, to investigate learning output on 10th grade SMAN 1 Terisi by using learning cycle with LKPD on main discussion of mathematical logic, to investigate the different output in experimented class and in controlled class. Population of the research are 10th grade SMAN 1 Terisi Indramayu numbering 185 students. Research sample is selected using cluster random sampling technique, and class X-2 is chosen as experimented class using learning cycle with LKPD and class X-1 is as controlled class using expository learning model as the sample. The research is quantitative and the techniques of collecting data are questionnaire and test. Technique of analyzing data used normality test, homogeneity test, hyphotesis test (t-tes). Data of finished questionnaire shows that average score of respond indicator and student motivation towards learning cycle with LKPD is 77,68 %, and it is categorized active. The result of linear regression test shows score of regression coeficient R=0,215, and score F=1,362 with sig=0,253. It is concluded from the data that there is influence on applying learning cycle with LKPD. On learning test, experimented class show they are better than controlled class. The average of learning output achieved by experimented class is 82,83 and that of controlled class is 75,7. It shows learning output divergence as much as 7,13. Based on hypothesis test, it is achieved score of statistical test sig.(2-tailed) which is 0,005<0,05 that Ho is denied. It means learning output in experimented class applying learning cycle with LKPD and controlled class implementing expository on main discussion over mathematical logic in 10th grade SMAN 1 Terisi Indramayu differs. Keywords: Learning Cycle, Student’s text book (LKPD), and Learning Output